RMB currency risk management after China's '8.11' exchange rate reform. Issue 9 (21st May 2021) - Peng, Yuliu; Kang, Wenru
ABSTRACT: After '8.11' RMB exchange rate reform in 2015 in China, RMB experienced two phases of irrational and pro-cyclical depreciation. The currency risk management of China's central bank shifted from quantitative management to price management step by step. The article analyzes the efficiency of China's central bank' management, and finds that the management improved the imbalance between supply and demand and reduced irrational and procyclical expectation on RMB exchange rate.